Increasing Employee Productivity: Analysis Employee Engagement - Wariati, Ambar (Green Publisher, 2024)
Employee productivity improvement article: analysis of employee engagement in the scope of human resource management science. This article aims to make a hypothesis related to the relationship between factors, which can then be used for further research in the field of human resource management. The approach used in this study is descriptive qualitative. The data used in this study comes from previous studies that are still relevant to the current investigation. Data were collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sinta journals. The results of this literature study include: 1) Competence has an effect on Increasing Employee Engagement; 2) Discipline has an effect on Increasing Employee Engagement; 3) Job Satisfaction has an effect on Increasing Employee Engagement; 4) Competence has an effect on Increasing Employee Productivity; 5) Discipline has an effect on Increasing Employee Productivity; 6) Job Satisfaction has an effect on Increasing Employee Productivity; and 7) Employee Engagement has an effect on Increasing Employee Productivity.